Inequality in Australia - Greig, Alastair, 1960- (Cambridge University Press, 2003)
This text seeks to analyse and explain inequality, challenging traditional conceptions and providing a new critical perspective. The authors provide a comprehensive historical account of inequality, and show how that account no longer adequately explains the new and different forms of inequality experienced in recent decades.